Coffee and Cholesterol - Impact of Brewing Methods - Svatun, Åsne Bjørk Lirhus (UiT Norges arktiske universitet, 2021)
Objective/methods: Coffee, especially boiled/plunger coffee, raises serum cholesterol (S-TC and S-LDL) because of its diterpenes, cafestol and kahweol. Epidemiological research comparing all the different brewing methods’ impact on serum cholesterol was still yet to be done. The aim of this study was to quantify the association between serum total cholesterol and serum low-density lipoprotein (S-TC and S-LDL) cholesterol and consummation of variously brewed coffee. By taking a cross-sectional epidemiological approach, using data from the 7th survey of the Tromsø Study (Tromsø 7, 2015-2016), we assessed 6,816 women and 7,309 men. Using multivariable linear regression models, the goal was to obtain knowledge on how much brewing method impacted serum cholesterol, and whether there was any difference in the associations between the various brewing methods and serum cholesterol. Results: Boiled coffee consumption is associated with increased S-TC and S-LDL cholesterol for both women and men. Consuming 6-8 cups of boiled/plunger coffee per day increased S-TC with 0.20 mmol/L and S-LDL 0.18 mmol/L for women and S-TC 0.27 mmol/L S-LDL 0.26 mmol/L for men (p0.001), compared to subjects not drinking boiled/plunger coffee. Similarly, consumption of 6-8 cups of filtered coffee per day is associated with increased S-TC in women (0.10 mmol/L, 95%CI=0.01-0.20) but not in men, compared to subjects drinking 0 cups. However, when changing inclusion criteria to include all subjects answering questions regarding filtered coffee, nonsignificant associations were observed. Intake of 3-5 cups of espresso daily is associated with increased S-TC (0.16 mmol/L, 95%CI=0.07-0.25) and S-LDL (0.13 mmol/L, 95%CI=0.05-0.22) in men but not in women, compared with subjects drinking 0 cups of espresso per day. This association becomes stronger with increasing espresso consumption in men. Instant coffee consumption had no clinically significant association with S-TC and S-LDL. Conclusion: Boiled and plunger coffee, espresso, filtered coffee, and ...